1999
DOI: 10.1074/jbc.274.14.9392
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Peptides Do Not Form Peptide-derived Free Radicals Spontaneously, but Can Enhance Metal-catalyzed Oxidation of Hydroxylamines to Nitroxides

Abstract: As the leading cause of dementia, Alzheimer's disease (AD) 1 is characterized by a loss of memory and neurons. These characteristics have been associated with brain lesions known as neurofibrillary tangles composed of Tau protein and amyloid plaques, which consist of amyloid ␤ (A␤) peptide. In a small number of families, mutations in the genes for the amyloid peptide precursor (APP, chromosome 21) to A␤ peptide for presenilin-1 (PSEN-1, chromosome 14), presenilin-2 (PSEN-2, chromosome 1) and for an anonymous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 37 publications
3
59
1
Order By: Relevance
“…all of which are associated with the autoxidation of these compounds and are thought to mediate their cytotoxicity (50,51). In addition, A␤-peptides have been shown to enhance the oxidation of hydroxylamine derivatives without the formation of peptide-derived free radicals (52). The results presented in this paper suggest that autoxidation products of apomorphine and its derivatives could exacerbate A␤ toxicity by stabilizing toxic A␤ protofibrillar intermediates.…”
Section: Table I Summary Of the Time-dependent Svau Studies Of A␤ In mentioning
confidence: 74%
“…all of which are associated with the autoxidation of these compounds and are thought to mediate their cytotoxicity (50,51). In addition, A␤-peptides have been shown to enhance the oxidation of hydroxylamine derivatives without the formation of peptide-derived free radicals (52). The results presented in this paper suggest that autoxidation products of apomorphine and its derivatives could exacerbate A␤ toxicity by stabilizing toxic A␤ protofibrillar intermediates.…”
Section: Table I Summary Of the Time-dependent Svau Studies Of A␤ In mentioning
confidence: 74%
“…Tempol also protected mice from developing Parkinsonian symptoms induced by administration of 6-OHDA. A study of several toxic brain peptides associated with Alzheimer's revealed that they were capable of oxidizing the nitroxide Tempone [86] although the significance of this finding is difficult to ascertain, however, as they do not spontaneously produce free radicals and the contribution of ROS to the development of Alzheimer's is not well characterized [86].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…The three histidine residues of amyloid-b at position 6, 13, and 14 and one tyrosine residue at position 10, all located in the hydrophilic N-terminal part of the peptide [43,44], behave as iron binding sites. The iron bound to these sites has been shown to generate H 2 O 2 by the Fenton reaction [45][46][47]. Not only production of ROS but also binding of iron to these residues induces amyloid-b aggregation.…”
Section: Iron Deposition and Senile Plaquesmentioning
confidence: 99%